The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2021
DOI: 10.1016/j.ijrobp.2020.11.046
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-Mediated Gemcitabine Delivery Reduces the Normal-Tissue Toxicity of Chemoradiation Therapy in a Muscle-Invasive Bladder Cancer Model

Abstract: Purpose Chemoradiation therapy is the standard of care in muscle-invasive bladder cancer (MIBC). Although agents such as gemcitabine can enhance tumor radiosensitivity, their side effects can limit patient eligibility and treatment efficacy. This study investigates ultrasound and microbubbles for targeting gemcitabine delivery to reduce normal-tissue toxicity in a murine orthotopic MIBC model. Materials and Methods CD1-nude mice were injected orthotopically with RT112 b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 35 publications
(15 reference statements)
0
8
0
Order By: Relevance
“…This significantly improves treatment efficiency and reduces systemic toxicity and drug side effects, rendering it the tumor-targeted therapy strategy with the most promising potential at present. [33][34][35] In this study, ultrasound NBs were used as drug delivery carriers. Based on the bridging effect between biotin-streptavidin, PD-L1 mAb/DOX-NBs were successfully prepared with a small and uniform particle size, high antibody connection rate, and good safety in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…This significantly improves treatment efficiency and reduces systemic toxicity and drug side effects, rendering it the tumor-targeted therapy strategy with the most promising potential at present. [33][34][35] In this study, ultrasound NBs were used as drug delivery carriers. Based on the bridging effect between biotin-streptavidin, PD-L1 mAb/DOX-NBs were successfully prepared with a small and uniform particle size, high antibody connection rate, and good safety in vivo.…”
Section: Discussionmentioning
confidence: 99%
“… MRI-guided focused ultrasound enhanced doxorubicin delivery by 4-fold compared to controls and significantly suppressed the volumetric tumor growth rate (24.4 ± 10.9%). Ruan (2021) [131] Gemcitabine Murine bladder tumor model (RT112 cells) Microbubble: diameter data not given Conc. : 3 × 10 8 /mL Freq.…”
Section: Cavitation-mediated Drug Deliverymentioning
confidence: 99%
“…For chemotherapy alone, cavitation selectively and efficiently enhanced the accumulation (4–8-folds) of drugs (paclitaxel, doxorubicin, gemcitabine, etoposide, and hydroxychloroquine) in tumor regions to improve the therapeutic efficiency [12] , [13] , [129] , [130] , [131] , [132] . Idbaih et al reported a first-in-man clinical trial in patients with recurrent glioblastoma of the cavitation-enhanced trans -BBB delivery of a chemotherapeutic drug (carboplatin).…”
Section: Cavitation-mediated Drug Deliverymentioning
confidence: 99%
“…US-mediated drug delivery methods hardly exacerbate the acute intestinal toxicity using the crypt assay in contrast to conventional chemoradiation. 93 In another gemcitabine delivery study, in vitro and in vivo RT112 bladder cancer cell line and murine orthotopic muscle-invasive bladder cancer model was tested. No significant increase in drug uptake was observed due to the US when compared to drug control of Drug+MBs.…”
Section: Interaction Of Ultrasound Withmentioning
confidence: 99%
“…Another study used US+MBs for targeted gemcitabine delivery to minimize normal-tissue toxicity in a mouse orthotopic MIBC model. US-mediated drug delivery methods hardly exacerbate the acute intestinal toxicity using the crypt assay in contrast to conventional chemoradiation . In another gemcitabine delivery study, in vitro and in vivo RT112 bladder cancer cell line and murine orthotopic muscle-invasive bladder cancer model was tested.…”
Section: Interaction Of Ultrasound With Biological Systems: Physical ...mentioning
confidence: 99%